Plastic Waste Management Due to Tourism Activities as an Efforts to Control Marine Pollution on Kuta Beach, Badung Regency - Ni Wayan Yudiani; Nyoman Diah Utari Dewi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Kuta Beach, one of Bali's most iconic coastal destinations, faces severe environmental challenges due to the rapid growth of tourism and inadequate waste management, often leading to a "plastic apocalypse" scenario, especially during the monsoon season. This study analyzes the relationship between high tourist influx and the accumulation of marine debris, which is heavily dominated by plastic waste generated from both tourism activities and seasonal ocean currents. The research highlights that the traditional "collect-haul-dispose" system is inefficient to handle the volume of waste, which significantly reduces the beach's aesthetic appeal and threatens marine ecosystems. Using a descriptive qualitative approach, this research evaluates the role of stakeholders, including government and local communities, in implementing cleaner, sustainable waste management strategies. The findings suggest that a comprehensive, circular economy approach, combined with stricter, eco-friendly infrastructure, is necessary to maintain Kuta Beach's sustainability as a top tourist destination. Keywords: Waste Management, Kuta Beach, Tourism Impact, Plastic Pollution, Sustainable Tourism, Bali.